TINJAUAN PENGGUNAAN SINGKATAN PADA PENULISAN TINDAKAN KEDOKTERAN DI SURAT PERSETUJUAN TINDAKAN KEDOKTERAN DI RUMAH SAKIT YADIKA JAKARTA SELATAN - Ima Rusdiana; Rizkia Larasati (APIKES Bhumi Husada Jakarta, 2022)
Based on the results of initial observations in April 2020 at the Yadika Hospital South Jakarta from the results of research on the use of abbreviations in writing medical actions in medical treatment approval letters, in January-March 65 medical records were found that used abbreviations of 13 (20%), namely the abbreviation for SC (sectio caesarea) is 12 (18%), PP (postpartum) is 1 (2%) and 52 (80%). Therefore, the researcher wants to know how the description of the use of abbreviations in writing medical actions in medical action approval letters. The method used is descriptive method. The results of the study according to quantitative analysis with a sample of 66 medical action approval forms obtained that use abbreviations of 30 (45%) while those who do not use abbreviations are 36 (55%), namely the abbreviation SC (sectio caesarea) as many as 26 (39%) and PP (postpartum) as many as 4 (6%). Keywords: abbreviation, medical approval, surgical patient